Synthesis without syntactic templates - Polgreen, E (2019)
Program synthesis is the mechanised construction of software. One of the main difficulties is the efficient exploration of the very large solution space, and tools often require a user-provided syntactic restriction of the search space. Writing such templates is often challenging, particularly since any constants required in the solution must be given in the template. In this dissertation we explore the research hypothesis that synthesis of programs without provision of such syntactic templates is computationally feasible using methods based on CounterExample Guided Inductive Synthesis (CEGIS).